Distribution of “model” congenital malformations in children whose mothers used to live in the environmentally unfavorable areas - Vlasova, Olena; Lastivka, Iryna (Journal of Education, Health and Sport, 2018)
Abstract. To determine the frequency of “model” congenital malformations in children whose mothers used to live in places with different geochemical characteristics in Chernivtsi and to define the risk indices of their formation. Material and methods. Retrospective analysis was carried out on 117 protocols of dissections of newborns and fetuses with CM, who died in utero or after birth in 2004-2014 in Chernivtsi and 489 genetic records of children born in Chernivtsi with “model” birth defects were also analyzed. Results. A ten-year analysis showed that the frequency of “model” CM in Chernivtsi in general corresponds to the EUROCAT International Register indices, with the exception of multiple birth defects, which exceeded the European index by 2.4 times, hypospadias – by 6 times, and congenital hydrocephalus , the index of which was on the upper limit.Conclusions. A significant risk of the formation of birth defects of the heart, the central nervous system and the genitourinary system was detected in the structure of “model” congenital malformations, provided that the mothers lived in places of geochemical disadvantages. The mortality of males with congenital malformations was higher than that of female children.